2013
DOI: 10.1007/s11605-012-2043-y
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Contrast-Enhanced Intraoperative Ultrasonography (CE-IOUS) in Patients with Colorectal Liver Metastases after Preoperative Chemotherapy

Abstract: In patients undergoing surgery for colorectal liver metastases after chemotherapy, contrast-enhanced intraoperative ultrasonography improved both the sensitivity of intraoperative ultrasonography to detect liver metastases and the R0 hepatic resection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
2
26
0
4
Order By: Relevance
“…for PET-CT has been suggested for detecting distant metastases [28,29]. Contrast-enhanced intraoperative ultrasound has been shown to improve both the sensitivity of intraoperative ultrasonography to detect LM and the rate of complete resection of hepatic metastases in patients undergoing surgery for CRCLM after chemotherapy [30].…”
Section: The Role Of Imaging In the Detection Of Synchronous Crclmmentioning
confidence: 99%
“…for PET-CT has been suggested for detecting distant metastases [28,29]. Contrast-enhanced intraoperative ultrasound has been shown to improve both the sensitivity of intraoperative ultrasonography to detect LM and the rate of complete resection of hepatic metastases in patients undergoing surgery for CRCLM after chemotherapy [30].…”
Section: The Role Of Imaging In the Detection Of Synchronous Crclmmentioning
confidence: 99%
“…For the preoperative detection of CRLM after neoadjuvant chemotherapy and consecutive diffuse fatty infiltration of the liver, Kulemann et al found MRI to be superior to MDCT, especially for the detection of small lesions with sensitivities of 65% for CT vs 88% for MRI and for CRLM ≤ 10 mm of 11% for CT vs 66% for MRI [113]. CE-IOUS performed in patients treated with neoadjuvant chemotherapy improves sensitivity and R0 hepatic resection rate [114]. In case of disappearing CRLM (no longer detectable by preoperative imaging = complete clinical response) CE-IOUS might detect even small tumor residuals which is crucial to ensure true R0 resection [115].…”
Section: Ce-ious -Where Are We Today? Essential Tool or Problem Solvementioning
confidence: 99%
“…Summarized, CE-IOUS is still of high value and might be the most effective or even mandatory after preoperative chemotherapy for CRLM [47,114,119].…”
Section: Ce-ious -Where Are We Today? Essential Tool or Problem Solvementioning
confidence: 99%
“…Intraoperative US has emerged as a valuable additional US technique and has been shown to have a higher sensitivity and specificity than preoperative transabdominal US, especially when combined with contrast-enhanced intraoperative US (13). Intraoperative US has been shown to help detect new metastases in 33%-42% of cases, with the addition of contrast-enhanced intraoperative US helping detect "disappearing" liver metastases after chemotherapy (14). Some of the limitations of US include operator dependence; ambiguity in segmental localization, which is crucial for surgical planning; and poor performance in the presence of hepatic steatosis and diffuse and chronic hepatic disease.…”
Section: Imaging Of Metastases In Crc Ultrasonographymentioning
confidence: 99%